2006
DOI: 10.1002/ajhb.20546
|View full text |Cite
|
Sign up to set email alerts
|

Variation and causal factors of craniofacial robusticity in Patagonian hunter-gatherers from the late Holocene

Abstract: Fueguian-Patagonian skulls have been characterized as some of the most robust of any modern crania. However, the causal factors of such robusticity remain unsettled. We assess within- and among-sample cranial robusticity of seven samples from continental Patagonia and Tierra del Fuego, using geometric morphometric techniques. In addition, the biomechanical, phylogenetic, and climatic hypotheses proposed to account for robusticity in such samples are discussed. Two Amerindian samples of farmers and two early mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 59 publications
8
57
0
19
Order By: Relevance
“…Moreover, BIB high values (>24 cm) were observed in all the groups, and are characteristic of high latitude populations (Ruff 1994). Previous studies have also identified evidence of cold adaptation in Fuego-Patagonia groups (Bernal et al 2006;Pearson and Millones 2005). Although the differences in temperature between the areas West and East to the Andes are small, the differences in humidity are noticeable (Pisano 1977).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, BIB high values (>24 cm) were observed in all the groups, and are characteristic of high latitude populations (Ruff 1994). Previous studies have also identified evidence of cold adaptation in Fuego-Patagonia groups (Bernal et al 2006;Pearson and Millones 2005). Although the differences in temperature between the areas West and East to the Andes are small, the differences in humidity are noticeable (Pisano 1977).…”
Section: Discussionmentioning
confidence: 75%
“…One of them corresponds to a terrestrial, and the other one to a marine hunter-gatherer. Other studies have also identified unbalanced sex distribution in Fueguian and Patagonian samples (Bernal et al 2006). While a high degree of cranial robusticity in Patagonian samples, which could bias sex estimation, has been identified (Bernal et al 2006), genetic analyses of human remains in Fuego-Patagonia show a high degree of agreement between morphological and genetic estimates of assessment of sex (AlfonsoDurruty unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge about the evolutionary relationships among these populations allows for a greater control over other factors, such as the environmental variables, that might have influenced cranial size and shape. Previous studies have found large differences in adult body and cranial size among South American populations, which seem to be highly correlated with ecological variables, and particularly the diet (Béguelin, 2009;Perez and Monteiro, 2009;Bernal et al, 2006Bernal et al, , 2010. The broad pattern found suggests that adults belonging to agriculturalists possessed the smallest crania, with shorter and less robust faces, compared with the hunter-gatherers from the same region.…”
Section: Introductionmentioning
confidence: 78%
“…In more localized studies, environmental plasticity has been suggested to play a more relevant role in morphological differentiation (Relethford 2004a). Specific studies have suggested that some craniometric measurements and anatomical regions might be under the influence of long-term selection in response to climate conditions, especially when populations adapted to extremely cold conditions are considered (Beals et al 1984;Bernal et al 2006;Harvati and Weaver 2006;Hubbe et al 2009;Roseman 2004;Roseman and Weaver 2004). Significant correlations between specific craniometric measurements and environmental factors, such as altitude (Guglielmino-Matessi et al 1979;Rothhammer and Silva 1990) and lifestyle (Carlson and Van Gerven 1977;González-José et al 2005; but see Paschetta et al 2010), have also been described.…”
mentioning
confidence: 94%